2022
DOI: 10.2147/cmar.s384325
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcome and Safety of the TCX Regimen for Advanced Gastric Cancer: A Prospective Cohort Study

Abstract: Objective To evaluate the outcome and safety of the paclitaxel, carboplatin, and capecitabine (TCX) regimen in patients with advanced gastric cancer. Methods Advanced gastric cancer patients received the TCX regimen for up to six cycles, which were 3 weeks apart. Paclitaxel (175 mg/m2) was given over a 3-hour infusion, followed by carboplatin in a 1-hour infusion on day 1. Capecitabine (850 mg/m2) was given orally twice daily from day 1 to day 14. Primary endpoints were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…4 Although capecitabine ameliorates 5-Fu-induced adverse effects, recent clinical reports have revealed that capecitabine, both in monotherapy and combined therapy, could induce severe peripheral neuropathy, manifested as numbness, paresthesia, hypoesthesia and even somatization disorders. 5 Based on various clinical trials, the peripheral neuropathy rates caused by capecitabine range from 36% to 73%, 4,6,7 greatly lowering the patients' quality of life. To date, investigations of capecitabineinduced peripheral neurotoxicity have only focused on clinical symptoms without further mechanistic studies.…”
Section: Introductionmentioning
confidence: 99%
“…4 Although capecitabine ameliorates 5-Fu-induced adverse effects, recent clinical reports have revealed that capecitabine, both in monotherapy and combined therapy, could induce severe peripheral neuropathy, manifested as numbness, paresthesia, hypoesthesia and even somatization disorders. 5 Based on various clinical trials, the peripheral neuropathy rates caused by capecitabine range from 36% to 73%, 4,6,7 greatly lowering the patients' quality of life. To date, investigations of capecitabineinduced peripheral neurotoxicity have only focused on clinical symptoms without further mechanistic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy is one of the conventional treatments for advanced GC patients. Common chemotherapeutic agents include paclitaxel (doxorubicin or paclitaxel), capecitabine, fluorouracil ( 18 ). However, the clinical benefits are limited by the potential risk of injury from surgery, the toxicity of chemotherapeutic agents, and resistance to targeted drugs.…”
Section: Introductionmentioning
confidence: 99%